Educational Activities and a Competency Framework for Meeting New Challenges in Higher Education - Jaeger, Bjørn; Rudra, Amit (International Institute of Informatics and Cybernetics, 2013)
In his article we explore how educational institutions are faced with changes in the modern global business environment, and how this leads to need for changes in curricula for business schools and information systems schools. Most of academia still uses a strict disciplinary model of education resulting in a high degree of specialization within each discipline while the modern business environments require knowledge workers who can address problems that cut across disciplines on an increasingly global scale. Research papers and governmental reports call for more emphasis on particularly three interdisciplinary topics; 1) competencies in globalization issues, 2) communication/working in team, and 3) information literacy. The disciplines of business and in particular information systems education have received much attention in this respect with several calls for change. How to bring about such a change is, however, still an open question. This paper proposes to address this issue in two ways; by suggesting two new educational activities and by proposing a new educational interdisciplinary competency framework to guide curriculum development when including interdisciplinary topics.